Situating Generative Knowing Theory in an Emerging Performative Paradigm - Shannon Perry; Trisha Barefield (Adult Education Research Conference, 2025)
This presentation develops generative knowing theory by situating it within an emerging performative paradigm. We illustrate this connection through our own scholarship and explore further implications for adult educators.
Keywords: relational experience; posthuman subjectivities; complexity